(untitled) (International Journal of Economics Management and Social Science, 2026)
Since McCombs and Shaw’s landmark 1972 study of the Chapel Hill election, agenda-setting theory has been one of mass communication research’s most productive and enduring frameworks for understanding how media coverage shapes public perception of issue salience. In the digital era, algorithmic curation, platform-mediated fragmentation, and citizen journalism have fundamentally transformed the agenda-setting landscape, raising critical questions about whether, how, and for whom media still set agendas. This study implements agenda-setting theory in the context of digital news media in North Sumatra, Indonesia, employing a multi-method design that combines content analysis of 420 news items from four major digital news platforms (2 months), a panel survey measuring public issue salience (n = 384, two waves), and 24 semi-structured interviews with news consumers and digital editors. Findings demonstrate a significant but differentiated agenda-setting effect: the correlation between media agenda prominence and public issue salience is strong for hard news topics (r = 0.724, p < 0.001) but substantially weaker for social welfare issues (r = 0.412, p < 0.01), reflecting the influence of personal experience and interpersonal communication in issue perception formation. Second-level agenda setting—the transfer of issue attributes and frames—shows stronger effects than first-level salience transfer, suggesting that digital media’s primary influence in the contemporary environment may be less about what issues people think about and more about how they think about them. The study contributes a digital-era refinement of agenda-setting theory and proposes a contextual agenda-setting model that accounts for algorithmic mediation, partisan selective exposure, and platform-specific effect mechanisms. Keywords: agenda-setting theory; McCombs and Shaw; digital media; public perception; issue salience; media framing; North Sumatra; Indonesia; media effects